The function f(x)=(x+1)2 is reflected over the x-axis to create g(x) . Identify the equation for g(x) .(1 point) Responses g(x)=(−x+1)2 g left parenthesis x right parenthesis equals left parenthesis negative x plus 1 right parenthesis squared g(x)=−(x+1)2 g left parenthesis x right parenthesis equals negative left parenthesis x plus 1 right parenthesis squared g(x)=(−x−1)2 g left parenthesis x right parenthesis equals left parenthesis negative x minus 1 right parenthesis squared g(x)=−x2+1

1 answer

To reflect the function \( f(x) = (x + 1)^2 \) over the x-axis, we need to negate the entire function. Therefore, the equation for \( g(x) \) becomes:

\[ g(x) = -f(x) = -((x + 1)^2) \]

So, the correct answer is:

\[ g(x) = -(x + 1)^2 \]

Thus, the response that matches is:

g(x) = −(x+1)²